2021
DOI: 10.1186/s43008-021-00082-y
|View full text |Cite
|
Sign up to set email alerts
|

Melanin production and laccase mediated oxidative stress alleviation during fungal-fungal interaction among basidiomycete fungi

Abstract: Fungal-fungal interaction often leads to the change in metabolite profile of both the interacting fungus which may have potential implication in industry or agriculture. In the present study, we performed two sets of fungal-fungal interaction—Trametes coccinea (F3) with Leiotrametes lactinea (F9) and T. coccinea (F3) with T. versicolor (F1) to understand the changes in the metabolite profile during the interaction process and how this process impacts the hyphal/mycelial morphology of the participating fungi. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Investigations into the mechanisms of this phenomenon by Dullah et al. ( 2021 ), focusing on fungal–fungal interactions between species within the genera Trametes and Leiotrametes found that melanin and extracellular laccase production were both upregulated at the interaction zones, confirming in vitro that these white rot fungi are capable of melanogenesis, and that laccase production appears to correlate with that of melanin. Although these studies focused on white rot fungi, it should be noted that brown rot fungi can also be capable of producing similar biochemical results, as detailed by Riley et al.…”
Section: Extracellular Fungal Eumelanin Productionmentioning
confidence: 95%
“…Investigations into the mechanisms of this phenomenon by Dullah et al. ( 2021 ), focusing on fungal–fungal interactions between species within the genera Trametes and Leiotrametes found that melanin and extracellular laccase production were both upregulated at the interaction zones, confirming in vitro that these white rot fungi are capable of melanogenesis, and that laccase production appears to correlate with that of melanin. Although these studies focused on white rot fungi, it should be noted that brown rot fungi can also be capable of producing similar biochemical results, as detailed by Riley et al.…”
Section: Extracellular Fungal Eumelanin Productionmentioning
confidence: 95%
“…GO term enrichment analysis of the180 DEGs showed that seven GO terms (GO:0016491, GO:0016705, GO:0016682, GO:0016679, GO:0004601, GO:0016684, and GO:0016209) related to the ROS signaling pathway were significantly enriched (Figure S4). Genes involved in the ROS process, such as LAC (Dullah et al., 2021), P450 (Veith & Moorthy, 2018), and peroxidase PER (Veith & Moorthy, 2018), were upregulated in CAM7 but downregulated in the cam7 compared with HM‐1 under V. dahliae stress (Figure S4), suggesting that the contribution of GhCaM7 towards V. dahliae resistance in cotton might.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, upon infestation, excess ROS accumulate in the host body, leading to the peroxidation and de-lipidation of membrane lipids and damaging cellular structure and function. Finally, increased membrane permeability and the massive extravasation of intracellular solute molecules block the physiological metabolism of the host [44,80].…”
Section: Discussionmentioning
confidence: 99%
“…As such, MDA content around and at the lesion site was, respectively, 18.41 and 90.66 times higher than that in the healthy areas of the basidiocarp, indicating the beginning of lipid oxidation around the rot and severe lipid oxidation at the rot site. PPO and PAL are important defense enzymes, while MnP and laccase play a defensive role in fungi [44]. As shown in Figure 8, PPO activity around and at the lesion site was, respectively, 36.35 and 51.03 times higher than that in the healthy areas of the basidiocarp.…”
Section: Effect On Defense Enzyme Activitymentioning
confidence: 92%